Innovation in Police Logistics Governance to Improve Operational Service Efficiency at the Logistics Bureau of the East Java Regional Police - Nita Febrianti; Fedianty Augustinah; Sedarmayanti Sedarmayanti (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This research seeks to examine the innovative governance of police logistics to enhance the operational service efficiency at the Logistics Bureau of East Java Regional Police. The research context arises from the need to reform police logistics management to meet technological innovations and demands for public accountability. This research utilized a qualitative method featuring a case study approach, incorporating extensive interviews with logistics officers, operational personnel, and third-party providers, along with firsthand observations of digital logistics management systems. The results indicate that the adoption of the Integrated Logistic Management System (ILMS) and barcode tracking has improved transparency, distribution speed, and efficiency in operational budgets. Nonetheless, difficulties persist in human resource capability and interdepartmental collaboration. The dialogue suggests that these advancements correspond with adaptive governance theory, stressing bureaucratic adaptability in response to organizational shifts, and public service motivation, which underscores the importance of motivation and professionalism in enhancing the quality of public services. The research finds that digital innovation and performance-oriented assessment enhance the efficiency of police operational services. It suggests enhancing human resource capabilities, performance assessment systems, and collaboration among units to attain transparent, effective, and sustainable logistics management.